2022
DOI: 10.1101/2022.08.17.504308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Cellular Response to Destabilized Transthyretin Reveals Cell- and Amyloidogenic Protein-Specific Signatures

Abstract: In ATTR amyloidosis, transthyretin (TTR) protein is secreted from the liver and deposited as toxic aggregates at downstream target tissues. Despite recent advancements in treatments for ATTR amyloidosis, the mechanisms underlying misfolded TTR-mediated cellular damage remain elusive. In an effort to define early events of TTR-associated stress, we exposed neuronal (SH-SY5Y) and cardiac (AC16) cells to wild-type and destabilized TTR variants (TTRV122I and TTRL55P) and performed transcriptional (RNAseq) and epig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…[37] In doing so, we demonstrated that AC16 cells exposed to cardiomyopathy-associated κAL LC displayed a significantly higher number of differentially expressed genes than AC16 cells exposed to non-AL amyloidogenic proteins with no significant overlap in differentially regulated genes between study groups. [37] Herein, we used human induced pluripotent stem cell (iPSC)-derived cardiomyocytes to validate the gene expression changes of clinically relevant genes in cardiac dysfunction-related pathways that are differentially activated upon exposure to a cardiomyopathy-associated κAL LC. We then used this data to guide subsequent interrogation of our clinical dataset for measurable parameters that reflect gene expression changes observed in these cardiac dysfunction-related pathways.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…[37] In doing so, we demonstrated that AC16 cells exposed to cardiomyopathy-associated κAL LC displayed a significantly higher number of differentially expressed genes than AC16 cells exposed to non-AL amyloidogenic proteins with no significant overlap in differentially regulated genes between study groups. [37] Herein, we used human induced pluripotent stem cell (iPSC)-derived cardiomyocytes to validate the gene expression changes of clinically relevant genes in cardiac dysfunction-related pathways that are differentially activated upon exposure to a cardiomyopathy-associated κAL LC. We then used this data to guide subsequent interrogation of our clinical dataset for measurable parameters that reflect gene expression changes observed in these cardiac dysfunction-related pathways.…”
Section: Introductionmentioning
confidence: 73%
“…Previously, we characterized neuronal SH-SY5Y and cardiac AC16 cells to an amyloidogenic, cardiomyopathy-associated kappa 1 LC (cardiomyopathy-associated κAL LC) as compared to amyloidogenic transthyretin (TTR) via RNA sequencing (RNAseq). [37] In doing so, we demonstrated that AC16 cells exposed to cardiomyopathy-associated κAL LC displayed a significantly higher number of differentially expressed genes than AC16 cells exposed to non-AL amyloidogenic proteins with no significant overlap in differentially regulated genes between study groups. [37] Herein, we used human induced pluripotent stem cell (iPSC)-derived cardiomyocytes to validate the gene expression changes of clinically relevant genes in cardiac dysfunction-related pathways that are differentially activated upon exposure to a cardiomyopathy-associated κAL LC.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Beginning soon after their initial discovery, iPSCs have been used to model diseases as well as screen drugs for the treatment of amyotrophic lateral sclerosis 9 , spinal muscular atrophy 10 , and other neurodegenerative 11 and muscular 12 disorders. Notably and importantly, these model systems have been applied to and faithfully recapitulate disease pathologies associated with aging that manifest late in life, such as in AD [13][14][15][16][17] and in our own work on familial ATTRamyloidosis [18][19][20][21] . The versatility in these systems to produce any cell and tissue type of the body allows for interrogation of multiple, aging-impacted tissues, many of which have been demonstrated to age at different rates 22 .…”
mentioning
confidence: 99%